Achieving Triple Aim Outcomes: An Evaluation of the Texas Medicaid Waiver. (June 2020) - Revere, Lee; Kavarthapu, Nina; Hall, Jessica; Begley, Charles
The Texas Medicaid Waiver, via the Delivery System Reform Incentive Payment (DSRIP) program, has provided a path for Texas to achieve the Triple Aim through its focus on a defined population at the project and system levels, and financial payment policy based on outcomes. Both iterations of the DSRIP program (Waiver 1.0 and 2.0) have helped define populations, created regional collaboration that sets the stage for a true integrator, and provided financial incentives for improving population health, enhancing patient experience, and controlling costs. The flexible design of project menus and measure bundles in DSRIP encouraged a variety of projects, numerous measures of success and (often) overlapping populations of individual served to achieve the ultimate goal of the Triple Aim. This research outlines the major features of Texas DSRIP and demonstrates the Medicaid Waiver effectively contributed to measurable improvements in health, suggesting Texas safety net providers are moving closer to Triple Aim achievement.